Correlation between racquet conversion speed with hand–eye coordination and reaction in amateur badminton players—an observational study - Charuhasini Mahapatra; Krishna Chandra Pradhan (Bulletin of Faculty of Physical Therapy)
Abstract Background Badminton is the fastest racquet sport and a multidirectional game requiring physical fitness and mental alertness. The mind-body connection is necessary to improve performance in badminton. Players have 0.1 s to react to the opponent’s attack in the defensive position. During racquet conversion from forehand to backhand grip players face more difficulty and multiple factors affect the conversion time like joint range of motion, wrist flexibility, wrist muscle strength, and coordination. The purpose of this study was to evaluate the correlation between quick grip change with coordination and reaction. Method A totalA total of 60 participants (38 boys and 22 girls) badminton players in the age group of 10–20 years were included in the study based on the selection criteria. For conversion speed sudden change in the grip using a racquet, for eye-hand coordination wall ball toss test using a tennis ball, and for reaction ruler drop test. of 60 participants (38 boys and 22 girls) badminton players in the age group of 10–20 years were included in the study based on the selection criteria. For conversion speed sudden change in the grip using a racquet, for eye-hand coordination wall ball toss test using a tennis ball, and for reaction ruler drop test. Result Pearson correlation was used to analyze the data which shows a high correlation between conversion speed and coordination (r = 0.881, p < 0.001)and a strong negative correlation between conversion speed and reaction(r = −0.731, p < 0.001). Conclusion It can be concluded from the results of this study that there is a strong correlation between conversion time and eye-hand coordination whereas conversion speed and reaction time have a strong and negative correlation. So, it shows when coordination improves conversion speed increases automatically but no such changes in the reaction case.